Asuhan Keperawatan Pada Ny. S Keluarga Tn. N Dengan Gangguan Sistem Kardiovaskuler : Hipertensi Di Desa Purwodadi RT 04 RW 04 Kecamatan Tonjong Kabupaten Brebes - Vina Rohmatul Ummah; Ahmad Zakiudin; Anna Maulina Lestari (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Post-cesarean section (SC) patients with premature rupture of membranes (PROM) require comprehensive nursing care due to their high risk of pain, infection, and limited mobility. This case study aims to describe the nursing care process applied to a 39-year-old woman post-SC with PROM indication. The study was conducted over five days in Nusa Indah Room at RSUD dr. Soeselo, Tegal. Data collection included interviews, observation, physical examination, and medical record review. The nursing interventions were guided by the Indonesian Nursing Diagnosis Standards (SDKI), Interventions (SIKI), and Outcomes (SLKI). Results showed a reduction in pain scale from 6 to 2, improved mobility, and wound healing without signs of infection or bleeding. These findings indicate that structured and holistic nursing care, combined with patient education and family involvement, can significantly enhance recovery outcomes. The implications suggest the need for clinical protocols in managing post-SC patients with PROM to ensure consistent, evidence-based nursing practice.